Environmental controls on the boron and strontium isotopic composition of aragonite shell material of cultured Arctica islandica - Y.-W. Liu; S. M. Aciego; A. D. Wanamaker Jr. (Biogeosciences, 2015)
Ocean acidification, the decrease in ocean pH associated with increasing atmospheric CO2, is likely to impact marine organisms, particularly those that produce carbonate skeletons or shells. Therefore, it is important to investigate how environmental factors (seawater pH, temperature and salinity) influence the chemical compositions in biogenic carbonates. In this study we report the first high-resolution strontium (87Sr / 86Sr and δ88 / 86Sr) and boron (δ11B) isotopic values in the aragonite shell of cultured Arctica islandica (A. islandica). The 87Sr / 86Sr ratios from both tank water and shell samples show ratios nearly identical to the open ocean, which suggests that the shell material reflects ambient ocean chemistry without terrestrial influence. The 84Sr–87Sr double-spike-resolved shell δ88 / 86Sr and Sr concentration data show no resolvable change throughout the culture period and reflect no theoretical kinetic mass fractionation throughout the experiment despite a temperature change of more than 15 °C. The δ11B records from the experiment show at least a 5‰ increase through the 29-week culture season (January 2010–August 2010), with low values from the beginning to week 19 and higher values thereafter. The larger range in δ11B in this experiment compared to predictions based on other carbonate organisms (2–3‰) suggests that a species-specific fractionation factor may be required. A significant correlation between the ΔpH (pHshell − pHsw) and seawater pH (pHsw) was observed (R2 = 0.35), where the pHshell is the calcification pH of the shell calculated from boron isotopic composition. This negative correlation suggests that A. islandica partly regulates the pH of the extrapallial fluid. However, this proposed mechanism only explains approximately 35% of the variance in the δ11B data. Instead, a rapid rise in δ11B of the shell material after week 19, during the summer, suggests that the boron uptake changes when a thermal threshold of > 13 °C is reached.